Show don't tell : stories - Sittenfeld, Curtis (Random House, 2025)
"In her second story collection, Sittenfeld shows why she's as beloved for her short fiction as she is for her novels. In these dazzling stories, she conjures up characters so real that they seem like old friends, laying bare the moments when their long held beliefs are overturned. In "The Patron Saints of Middle Age," a woman visits two friends she hasn't seen since her divorce. In "A for Alone," a married middle-aged artist embarks on a creative project intended to disprove the so-called Mike Pence Rule, which suggests that women and men can't spend time alone without lusting after each other. And in "Lost but Not Forgotten," Sittenfeld gives readers of her novel, Prep, a window into the world of her beloved character Lee Fiora, decades later, when Lee attends an alumni reunion at her boarding school. Hilarious, thought-provoking, and full of tenderness for her characters, Sittenfeld's stories peel back layer after layer of our inner lives, keeping us riveted to the page with her utterly distinctive voice"--